Retrait, refus, phobie scolaire : du mal-être au « désarrimage scolaire » - Nadine Demogeot (Recherches en Éducation)
We present here a few thoughts on ill-being at school, looking at the phenomena of « withdrawal, refusal or phobia from school », problems that have been on the increase over the last ten years or so, revived by the health context of Covid 19, and for which the psychologists of the French Ministry of Education are frequently called upon. The aim is to understand the suffering of these pupils, some of whom have dropped out of school altogether, and to examine the way in which schools operate today in an attempt to understand the educational « disarray » experienced by these young people. We propose to centre our reflections around three axes: the first refers to theoretical references concerning fear of school and the issue of school phobia. The second axis invites us to return to the central place of the pedagogical relationship and the quality of the teacher-pupil bond as a means of re-anchoring. Finally, in the third part, we mention other ways of supporting these disaffected young people and the research prospects to be explored with a view to prevention.